Mulheres trabalhadoras em uma fábrica recuperada: mudanças e permanências na organização e gestão do trabalho - Roseli de Fátima Corteletti; Jacob Carlos Lima (Ciências Sociais Unisinos)
The industrial restructuring of the 1990s in Brazil forced many workers to seek “new” work strategies to face unemployment. Among these strategies, the self-management constituted a possibility to avoid informality and guarantee income. In this context, several factories were recovered by the workers and transformed into cooperatives. In this article, we seek to analyze the work and daily life of the working women of a textile cooperative located in the southern region of Brazil. The objective was to verify the changes in the management and organization of labor, in view of the previous situation as a regular company and how women were involved in this process. Interviews were conducted with 27 cooperatives, aged between 35 and 75 years, and collected data on the history of the factory and the transition process. We found that the change in management did little in terms of the working conditions and the personal and social. life of women workers. The fact that they were “collective owners” of the means of production did not guarantee them greater autonomy and freedom at work, or any change in the sexual division of labor.